2007
DOI: 10.1007/s10637-007-9080-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of the heparanase inhibitor PI-88 in patients with advanced melanoma

Abstract: Treatment options for advanced melanoma are limited. PI-88, a potent inhibitor of heparanase, demonstrates anitangiogenic properties and has shown activity against melanoma in phase I studies. This was an open-label, multicenter, phase II study of PI-88 in patients with advanced melanoma. Patients received a fixed-dose of 250 mg/day given subcutaneously for four consecutive days followed by three drug-free days per week in a 28-day cycle. A total of 44 patients were enrolled in the intent to treat population, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…PI-88, a potent inhibitor of heparanase, demonstrates an overall survival and time to progression similar to standard chemotherapy (Basche et al, 2006). In a phase II trial (Lewis et al, 2008) a total of 44 patients were enrolled with about 60% of them previously treated. The median time to progression and overall survival was 1.7 months and 9 months, respectively.…”
Section: Antiangiogenic Therapiesmentioning
confidence: 99%
“…PI-88, a potent inhibitor of heparanase, demonstrates an overall survival and time to progression similar to standard chemotherapy (Basche et al, 2006). In a phase II trial (Lewis et al, 2008) a total of 44 patients were enrolled with about 60% of them previously treated. The median time to progression and overall survival was 1.7 months and 9 months, respectively.…”
Section: Antiangiogenic Therapiesmentioning
confidence: 99%
“…Hence, heparanase is a highly specific target for anticancer therapy; if successfully suppressed, inhibition of tumor growth, metastasis, and angiogenesis is expected to ensue (29,30). Several inhibitors of heparanase were developed mainly through screening of sulfated compounds, of which PI-88 is being tested in clinical trials (31). A glycol-split N-acetylated heparin (32) has been demonstrated to be highly effective in myeloma tumors (33) and will soon enter clinical trials.…”
Section: Alternative Splicing As An Evolutionary Path To Cope With Stmentioning
confidence: 99%
“…On the other hand, PI-88 which is primarily composed of highly sulfated oligomannose generated from yeast turns to be the most potential novel antitumor pharmaceutical exhibiting excellent antiangiogenic and anti-metastatic activities (33). PI-88 was initially developed by Progen while the Phase III clinical trial of PI-88 in hepatocellular carcinoma patients has been conducted all around the world by Taiwan Medigen Biotechnology Corporation since 2011 (34)(35)(36). Medigen reported that the treatment of patients was nearly completed and desirable results were expected.…”
Section: Carbohydrate Drugs In Developmentmentioning
confidence: 99%